Factors influencing the expression of human directed dog aggression. A qualitative study of professional opinion - Helen Howell; Ann Baslington-Davies; Daniel S. Mills; Todd E. Hogue (Applied Animal Behaviour Science, 2026)

Risk factors for human-directed aggression by dogs: The human side of the problem. A two-part systematic review and narrative synthesis - Helen Howell; Ann Baslington-Davies; Daniel S. Mills; Todd E. Hogue (Applied Animal Behaviour Science, 2025)

Extended gene panel testing in lobular breast cancer - Elke M. van Veen; D. Gareth Evans; Elaine F. Harkness; Helen J. Byers; Jamie M. Ellingford; Emma R. Woodward; Naomi L. Bowers; Andrew J. Wallace; Sacha J. Howell; Anthony Howell; Fiona Lalloo; William G. Newman; et al. (Familial Cancer, 2022)
Purpose : Lobular breast cancer (LBC) accounts for ~ 15% of breast cancer. Here, we studied the frequency of pathogenic germline variants (PGVs) in an extended panel of genes in women affected with LBC. Methods : 302 women with LBC and 1567 without breast cancer were tested for BRCA1/2 PGVs. A subset of 134 LBC affected women who tested negative for BRCA1/2 PGVs underwent extended screening, including: ATM, CDH1, CHEK2, NBN, PALB2, PTEN, RAD50, RAD51D, and TP53. Results : 35 PGVs were identified in the group with LBC, of which 22 were in BRCA1/2 . Ten actionable PGVs were identified in additional genes ( ATM (4), CDH1 (1), CHEK2 (1), PALB2 (2) and TP53 (2)). Overall, PGVs in three genes conferred a significant increased risk for LBC. Odds ratios (ORs) were: BRCA1 : OR = 13.17 (95%CI 2.83–66.38; P = 0.0017), BRCA2 : OR = 10.33 (95%CI 4.58–23.95; P < 0.0001); and ATM: OR = 8.01 (95%CI 2.52–29.92; P = 0.0053). We did not detect an increased risk of LBC for PALB2, CDH1 or CHEK2 . Conclusion : The overall PGV detection rate was 11.59%, with similar rates of BRCA1/2 (7.28%) PGVs as for other actionable PGVs (7.46%), indicating a benefit for extended panel genetic testing in LBC. We also report a previously unrecognised association of pathogenic variants in ATM with LBC.

Enhancing the TurtleWatch product for leatherback sea turtles, a dynamic habitat model for ecosystem‐based management - Evan A. Howell; Aimee Hoover; Scott R. Benson; Helen Bailey; Jeffrey J. Polovina; Jeffrey A. Seminoff; Peter H. Dutton (Fisheries Oceanography, 2015)
Fishery management measures to reduce interactions between fisheries and endangered or threatened species have typically relied on static time‐area closures. While these efforts have reduced interactions, they can be costly and inefficient for managing highly migratory species such as sea turtles. The NOAA TurtleWatch product was created in 2006 as a tool to reduce the rates of interactions of loggerhead sea turtles with shallow‐set longline gear deployed by the Hawaii‐based pelagic longline fishery targeting swordfish. TurtleWatch provides information on loggerhead habitat and can be used by managers and industry to make dynamic management decisions to potentially reduce incidentally capturing turtles during fishing operations. TurtleWatch is expanded here to include information on endangered leatherback turtles to help reduce incidental capture rates in the central North Pacific. Fishery‐dependent data were combined with fishing effort, bycatch and satellite tracking data of leatherbacks to characterize sea surface temperature ( SST ) relationships that identify habitat or interaction ‘hotspots’. Analysis of SST identified two zones, centered at 17.2° and 22.9°C, occupied by leatherbacks on fishing grounds of the Hawaii‐based swordfish fishery. This new information was used to expand the TurtleWatch product to provide managers and industry near real‐time habitat information for both loggerheads and leatherbacks. The updated TurtleWatch product provides a tool for dynamic management of the Hawaii‐based shallow‐set fishery to aid in the bycatch reduction of both species. Updating the management strategy to dynamically adapt to shifts in multi‐species habitat use through time is a step towards an ecosystem‐based approach to fisheries management in pelagic ecosystems.

Alterations in peripheral muscle contractile characteristics following high and low intensity bouts of exercise - Martyn G. Morris; Helen Dawes; Ken Howells; Oona M. Scott; Mary Cramp; Hooshang Izadi (European Journal of Applied Physiology, 2012)

Muscle contractile characteristics: relationship to high-intensity exercise - Martyn G. Morris; Helen Dawes; Ken Howells; Oona M. Scott; Mary Cramp; Hooshang Izadi (European Journal of Applied Physiology, 2010)

Oceanographic influences on the dive behavior of juvenile loggerhead turtles (Caretta caretta) in the North Pacific Ocean - Evan A. Howell; Peter H. Dutton; Jeffrey J. Polovina; Helen Bailey; Denise M. Parker; George H. Balazs (Marine Biology, 2010)

Gait adaptations to simultaneous cognitive and mechanical constraints - Emad Al-Yahya; Helen Dawes; Johnathan Collett; Ken Howells; Hooshang Izadi; Derick T. Wade; Janet Cockburn (Experimental Brain Research, 2009)